2012
DOI: 10.1007/s10295-012-1177-y
|View full text |Cite
|
Sign up to set email alerts
|

Novel image cytometric method for detection of physiological and metabolic changes in Saccharomyces cerevisiae

Abstract: The studying and monitoring of physiological and metabolic changes in Saccharomyces cerevisiae (S. cerevisiae) has been a key research area for the brewing, baking, and biofuels industries, which rely on these economically important yeasts to produce their products. Specifically for breweries, physiological and metabolic parameters such as viability, vitality, glycogen, neutral lipid, and trehalose content can be measured to better understand the status of S. cerevisiae during fermentation. Traditionally, thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…46 Monitoring additional parameters using the currently developed platform can be easily performed by adding adequate fluorescence markers to the dilution buffer and recording the fluorescence signal in different wavelength bands. Besides viability, other physiological and metabolic parameters, such as apoptosis, hypoxia and other stress related conditions, can be quantified and used to enhance the efficiency of bioreactors.…”
Section: Discussionmentioning
confidence: 99%
“…46 Monitoring additional parameters using the currently developed platform can be easily performed by adding adequate fluorescence markers to the dilution buffer and recording the fluorescence signal in different wavelength bands. Besides viability, other physiological and metabolic parameters, such as apoptosis, hypoxia and other stress related conditions, can be quantified and used to enhance the efficiency of bioreactors.…”
Section: Discussionmentioning
confidence: 99%
“…The obtained results are in agreement with the results obtained by other authors using the manual method [11,17,30,31]. A comparison of the obtained linear interval and CV of Easycounter YC with other similar image cytometers showed that they have a similar CV, but the optimal interval is different for each different device: 1 Â 10 5 -2 Â 10 6 cells/mL with CV 3-10% for NucleoCounter YC-100 (company ChemoMetec) and 4 Â 10 6 -6.6 Â 10 7 cells/mL with CV 4-13% for Cellometer Auto X4 (10Â) (Nexcelom Bioscence) [11,23,28,31].…”
Section: Cell Count Linearity and Reliabilitymentioning
confidence: 99%
“…Currently, with the emergence of automated cell counters, researchers can analyze a large number of samples faster [15,16] and with less variability stemming from human-error. The development of computers, automation software, optics, fluorescent dyes and precision manufacturing techniques together with modern technologies such as flow cytometry and image cytometry, has helped to overcome many of the drawbacks associated with the hemacytometer [17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…The DNA content of yeast cells provides information about the cell cycle and is thus a powerful tool to assess the effects of propagation parameters on the yeast cell cycle and yeast physiology. FCM assays were developed for assessing the physiological status of the yeast cells during fermentation process [24,25]), for determination of yeast viability and cell number in a brewery [26][27][28][29][30][31][32], predictions of flocculation ability of brewer yeasts, separation of the prototroph yeast fusants [33], assessment of Saccharomyces cerevisiae vitality [34,35,36], detection of spoilage microorganisms [24,37], the influence of beer process conditions on beer stability [38], identification of haploid strains of industrial brewer's yeast, fermentation process control [20,39,40]. The use of FCM for age assessment of a yeast population and its application in beer fermentation was reviewed in the publication [41].…”
Section: Brewingmentioning
confidence: 99%